2023
DOI: 10.3389/fimmu.2023.1171649
|View full text |Cite
|
Sign up to set email alerts
|

Soluble biomarkers to predict clinical outcomes in non-small cell lung cancer treated by immune checkpoints inhibitors

Abstract: Lung cancer remains the first cause of cancer-related death despite many therapeutic innovations, including immune checkpoint inhibitors (ICI). ICI are now well used in daily practice at late metastatic stages and locally advanced stages after a chemo-radiation. ICI are also emerging in the peri-operative context. However, all patients do not benefit from ICI and even suffer from additional immune side effects. A current challenge remains to identify patients eligible for ICI and benefiting from these drugs. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 197 publications
0
5
0
Order By: Relevance
“…Thus, our research underscores the importance of neutrophil-related biomarkers in predicting NSCLC risk, offering valuable assistance in clinical diagnosis. NLR, a parameter derived from the NEU divided by the LYM, is one of the most widely investigated features based on blood cell counts and serves as an indicator of systemic inflammation [36]. NLR captures the balance between the detrimental effects of increased neutrophils and the beneficial roles of adaptive immunity mediated by lymphocytes [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our research underscores the importance of neutrophil-related biomarkers in predicting NSCLC risk, offering valuable assistance in clinical diagnosis. NLR, a parameter derived from the NEU divided by the LYM, is one of the most widely investigated features based on blood cell counts and serves as an indicator of systemic inflammation [36]. NLR captures the balance between the detrimental effects of increased neutrophils and the beneficial roles of adaptive immunity mediated by lymphocytes [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of cancer research, NLR serves as an effective indicator of the dynamic balance between pro-tumor and anti-tumor responses in the body. Most published studies have mainly focused on the correlation between NLR and the prognosis of NSCLC [36][37][38][39][40], with little attention paid to its association with disease risk. Therese Haugdahl Nøst et al conducted a study on approximately 440,000 participants based on data from the UK Biobank, evaluating the longitudinal relationships between four systemic inflammation indicators (NLR, systemic immune-inflammation index, platelet-to-lymphocyte ratio, lymphocyte-tomonocyte ratio) and the risk of 17 cancer sites diagnosed clinically in the years preceding the study [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies have explored the correlation between sPD-L1 levels and clinical factors in individuals with HNSCC. Research by Ancel et al has shown that high sPD-L1 levels in patients with non-small-cell lung cancer are associated with advanced stages of the disease and worse survival rates [ 43 ]. Similarly, Xu et al found that patients with advanced solid tumors tend to have higher levels of PD-L1 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLR has been used as an indicator of chronic inflammation and general immune response, and may contribute to evaluation of tumor response in patients treated with immunotherapy [22]. Therefore, we also evaluated the NLR among cStages, treatment strategies, and pathological response of neoadjuvant therapy.…”
Section: Lower T CM and Higher Exhausted T-cell Frequencies After Crtmentioning
confidence: 99%